Pelatihan Pembuatan Bunga Kawat Bulu dengan Inovasi Mutiara dan Lampu LED Bagi Mahasiswa Administrasi Bisnis Universitas Sahid Surakarta - Marshela Nur Rahma Zallyanti; Anggit Dyah Kusumastuti (Jurnal Kemitraan Masyarakat, 2025)
The training on making feather wire flowers with pearl and LED light innovations is a form of community service activity aimed at enhancing the entrepreneurial skills of fourth-semester students of the 2023 cohort in the Business Administration Program at Universitas Sahid Surakarta. This activity is motivated by the importance of developing students’ creativity and innovation in facing the challenges of the job market and opportunities in the creative business sector. The methods used include lectures, demonstrations, and hands-on practice. The results of the activity show that this training effectively increases students’ skills and interest in high-value handicrafts. It is expected that this activity can encourage students to become independent and innovative creative entrepreneurs.